Survival of Brånemark System Mk III implants and analysis of risk factors associated with implant failure. Issue 2 (February 2017) - Hasegawa, T.; Kawabata, S.; Takeda, D.; Iwata, E.; Saito, I.; Arimoto, S.; Kimoto, A.; Akashi, M.; Suzuki, H.; Komori, T.
Abstract: The purpose of this study was to retrospectively investigate the outcomes of Brånemark System Mk III TiUnite/Groovy implants placed in patients at Kobe University Hospital. Various risk factors for implant failure, including mechanical coupling, were investigated by univariate and multivariate analysis. The predictive variables investigated included age, sex, smoking habit, general health, history of radiation therapy, application of a dentomaxillary prosthesis, type of prosthesis, use of alveolar bone augmentation, site of implant insertion, mechanical coupling between implants, and the length and diameter of the implants. Of the 907 implants investigated, only 23 were unsuccessful; the overall survival rate was 96.7%. Increased age, radiation therapy, application of a removable prosthesis or dentomaxillary prosthesis, lack of mechanical coupling between implants, and shorter implants (≤8.5 mm) were significant risk factors for implant failure according to univariate analysis ( P  < 0.05). Multivariate analysis identified a significant association ( P  < 0.05) between dental implant failure and a lack of mechanical coupling between implants (odds ratio 6.88) and shorter implants (≤8.5 mm) (odds ratio 3.43). The findings of this study demonstrated multivariate relationships between various risk factors and dental implant failure.